K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 12 2017

[ ( 6 . x - 39 ) : 7 ] . 4 = 12

[ ( 6 . x - 39 ) : 7 ] = 12 : 4

( 6 . x - 39 ) : 7 = 3

6 . x - 39 = 3 . 7

6 . x - 39 = 21

6 . x = 21 + 39

6 . x = 60

x = 60 : 6

x = 10

Vậy x = 10

9 tháng 12 2016

a, x-7= -5

   x   = (-5)+7

   x = 2

Vậy x = 2

b, 128-3.(x+4)=23

          3.(x+4)=128-23

          3.(x+4)= 105

             x+4  = 105 : 3

             x+4  = 35

             x      =  35-4

             x      = 31

Vậy x =31

c, [(6x-39) :7].4=12

    [(6x-39):7]   = 12:4

    [(6x-39):7]   =  3

     6x-39        = 3.7

     6x - 39      =  21

     6x             = 21+39

     6x             = 60              

       x             = 60:6

       x             = 10 

Vậy x = 10

d, (x:3-4).5=15

    x:3-4   = 15 : 5

    x:3-4   = 3

    x: 3      = 7

    x          = 21

Vậy x= 21

9 tháng 12 2016

giúp mk với

25 tháng 6 2018

a) \(\frac{18}{45}-\frac{4}{12}-\frac{6}{9}-\frac{21}{35}=\frac{2}{5}-\frac{1}{3}-\frac{2}{3}-\frac{3}{5}\)

\(=\left(\frac{2}{5}-\frac{3}{5}\right)-\left(\frac{1}{3}+\frac{2}{3}\right)\)

\(=\frac{-1}{3}-1\)

\(=\frac{-4}{3}\)

b) \(\frac{4}{3}+\frac{3}{5}+\frac{7}{3}+\frac{2}{5}+\frac{1}{3}=\left(\frac{4}{3}+\frac{7}{3}+\frac{1}{3}\right)+\left(\frac{3}{5}+\frac{2}{5}\right)\)

\(=4+1=5\)

c) \(\frac{1}{3}.\frac{4}{5}.\frac{1}{3}.\frac{6}{5}=\frac{8}{75}\)

d) \(\frac{6}{7}.\frac{8}{13}+\frac{6}{7}.\frac{9}{13}-\frac{3}{13}.\frac{6}{7}\)

\(=\frac{6}{7}.\left(\frac{8}{13}+\frac{9}{13}-\frac{3}{13}\right)\)

\(=\frac{6}{7}.\frac{14}{13}\)

\(=\frac{12}{13}\)

20 tháng 9 2018

a) 7.x - x = 521 : 519 + 3.22 - 70

6x = 25 + 12 - 1

6x = 36

x = 6

b) 7x - 2x = 617 : 615 + 44 : 11

5x = 36 + 4

5x = 40

x = 8

20 tháng 9 2018

c) 5x + x = 39 - 311 : 39

6x = 39 - 9

6x = 30

x = 5

d) [(6x - 39) : 7]. 4 = 12

(6x - 39) : 7 = 12 : 4

(6x - 39) : 7 = 3

6x - 39 = 3 . 7

6x - 39 = 21

6x = 21 + 39

6x = 60

x = 10

x = 

7 tháng 12 2021
[(6x-39):7]=12:4 [(6x-39):7]=3 6x-39=3.7 6x-39=21 6x=21+39 6x=60 X=60:6 X=10
27 tháng 7 2015

a, 53 x 39 + 47 x 39 - 53 x 21 - 47 x 21

= 53 x (39-21) + 47 x (93-21)

=53 x 18 + 47 x 18

= (53 +47) x 18

=100 x 18

=1800

b,2 x 53 x 12 + 4 x 6 x 87 - 3 x 8 x 40

=24 x 53 + 24 x 87 - 24 x 40

=24 x (53+87-40)

=24 x 100

=2400

c,5 x 7 x 77 - 7 x 60 +49 x 25 -15 x 42.

=5 x 7 x 77 - 7 x 5 x 12 +49 x 5 x 5 - 5 x 3 x 42.

=5 x 539 - 84 x 5 +245 x 5 -5 x 126

=5 x (539 - 84 +245 -126)

=5 x 574

=2870

1 tháng 9 2016

tính nhanh cơ

9 tháng 9 2018

a,102

b,2400

c,2870

24 tháng 6 2018

1) x-7=-5 => x=-5+7 = 2

2) |x|=3 => x =3 hoặc x = -3

3) |x|+5=8 => |x| = 8-5=3

               => x = 3 hoặc x = -3

4) 8-x = 12 => x = 8-12 = -4

5) 6x-39=5628:28

=> 6x-39=201

=> 6x     = 201+39

=> 6x     = 240

=> x       = 40

6) 82+(200-x) = 123

=> 200-x  = 123 - 64

=> 200-x  = 59

=> x         = 200-59

=> x          = 141

7) x+10 = -14

=> x     = -14 - 10

=> x     = -24

8) 5x-12 = 48

=> 5x     = 48+12

=> 5x     = 60

=> x       = 12

24 tháng 6 2018

1) x = 2

2) x = 3 hoặc x = -3

3) x = 3 hoặc x = -3

4) x = -4

5) x = 40

6) x = 141

7) x = -24

8) x = 12 

\(a.\left[\left(6.x-39\right).7\right].4=12\)

\(\left(6.x-39\right).7=12:4\)

\(6.x-39=3:7\)

\(6.x=\frac{3}{7}+39\)

\(x=\frac{276}{7}:6\)

\(x=\frac{46}{7}\)

( câu a )

\(b.200-\left(2.x+6\right)=4^3\)

\(200-\left(2.x+6\right)=64\)

\(2.x+6=200-64\)

\(2.x=136-6\)

\(x=130:2\)

\(x=65\)

( câu b )